Equity valuation : the Boeing Company - Castro, João Pedro Rocha Alves Alvim de (2020)
This Master Thesis object is to place a value for the Equity of The Boeing Company (BA), one of the World’s largest aerospace and defense company’s. Out of the set of valuation methodologies, the Discounted Cash Flow (“DCF”) by means of a Free Cash Flow to Firm (“FCFF”) and Relative Valuation through EV/EBITDA and P/E, will be used. Emphasis will be given to the FCFF. The Boeing Company is facing challenging times, in light of the novel Coronavirus crisis. On top of a previous crisis the company faced by the grounding of it’s most important airplane, the 737 MAX. Given the high macroeconomic and company specific uncertainties, three scenarios and sensitivity analysis to critical variables were performed. The analysis performed, sustains the basis to the issue of a HOLD recommendation, with a price target of $132.5 for 30th June 2020. The scenarios considered and multiples approach, allow for a wider scope range between $92.8 and $173.5 for the PPS. The results were compared with those of a report issued by Refinitiv.